Perceived overqualification and turnover intention: The moderating role of leader support and cynicism - Neuneung Ratna Hayati; Imanirrahma Salsabil; Amin Wibowo; Kabul Wahyu Utomo; Usman Mika’il Usman (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This study aims to determine the relationship between perceived overqualification and turnover intention, exploring the gap in existing research by focusing on leader support and individual cynicism as context-specific influences on this relationship. This study uses a quantitative survey involving 135 respondents chosen explicitly from the service sector, including culinary, technology and IT, hospitality, and creative businesses spread across Indonesia. The empirical findings found that perceived overqualification can increase turnover intention, and this effect will be more substantial when individuals have cynicism toward the organization. However, when individuals feel supported by leaders, the effect becomes weaker. The results of this study suggest interventions can be made through leader support to weaken individual factors, specifically employee cynicism, which can amplify the adverse behavioral effects of employees' perceived over-qualifications. The findings must be generalized cautiously, including the potential for common method bias. This paper explains the interaction between perceived overqualification, turnover intention, leader support, and individual cynicism. The results contribute to the organizational psychology literature using the lens of person-job and person-organization fit theories.